REVITALIZING HERITAGE THROUGH DESIGN THINKING: STRATEGIC VALUE INITIATIVES FOR BATIK MAHKOTA LAWEYAN - Kiswardani, Wahyu Eka; Ghina, Astri (Transpublika Publisher, 2024)
Batik, one of Indonesia’s most important cultural heritages, requires maximum conservation. Meanwhile, Batik Mahkota Laweyan in Solo (Surakarta), Central Java, is the nation’s oldest handcrafted batik producer that specializes not only in hand-made products but also in activities related to education and tourism. This initiative is intended to increase the company’s market visibility. Despite these initiatives, the organization has struggled to fully realize its potential due to its numerous challenges. This research provides insights into the challenges faced by MSMEs, particularly the batik business. It suggests actionable solutions based on a design thinking framework and qualitative methods. The study conducted at Batik Mahkota Laweyan identified and prioritized the challenges, including weak branding in tourism and service knowledge. A brainstorming session generated 36 practical ideas for improvement. The research also highlights the branding opportunities in travel and education services, emphasizing timely implementation within budget constraints. It offers guidance on enhancing branding at Batik Mahkota Laweyan, and the interview questions could serve as a template for future research in similar businesses.